Mantra Pengasihan Tungtung Tangis Perspektif Bentuk Fungsi dan Makna - Pande Gede Brahmandika (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2021)
The purpose of this study was to describe the form, function and meaning of the pangasihan tungtung tangis mantra. This research uses functional structural theory and meaning theory. The method used is a qualitative method. The instruments used in this study were interviews, observations, in-depth literature study of the informants. Determination of informants using purposive sampling technique. The results of this study are: first, the tungtung tangis mantra as a subtle form of pangasihan is used to attract one's opponent to sympathy. In its development, the tungtung tangis mantra can be used as a chuckle or buntilan or gegemet (provision) to obtain someone's desire to be fulfilled. Second, the form of shading the target so that it is precisely the sasran to the recipient of the pangasihan tungtung tangis mantra.